Panoramic and Evaluation on the Articulation of the Innovations Introduced by the Regulation (EU) 2019/1111 Concerning Child Return Procedures in the Spanish Legal System - Calzado Llamas, Antonio Jesús (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This communication aims to contrast the most relevant innovations that Regulation (EU) nº. 2019/1111 introduces concerning the relationship with the 1980 Hague Convention, and the Spanish rules on the issue. We focus firstly on the normative interaction by analysing material, terri torial, personal and temporal scope. Followingly, it is analysed the interaction around the concept of international child abduction and its principal components, like the illegal transfer or removal, the rights of custody and the habitual residence. Finally, we evaluate the Spanish legislation in force by means of a contrast with the rules contained on Chapter III of the Regulation, enshrined to complement the return procedure. From this analysis, we conclude that the new Regulation enhances the previous legal framework, even it must be pointed that the Spanish legislator had already considered most of those new measures in our national legal system.